Response of Fonio (Digitaria exilis) Accessions to Fertilizer Application - Bawa, Alhassan; Kwahene Addai, Isaac; B. Bisuki, Konlan (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2022)
Fonio is one of the lost crops of Africa, and part of the reasons it has been neglected is inadequate information on Fonio growth and yield potential across its growing areas, hence the need to assess the response of available germplasm to fertilizer application. The objectives of the study were to determine the growth and yield response of Fonio accessions to fertilizer application, and to evaluate the interactive effect of fertilizer and Fonio accession on growth and yield. The study was conducted in Northern Ghana, during the 2019 cropping season. The research used a 4 x 5 (four fertilizer levels and five accessions) factorial experiment in a randomized complete block design with three replications. The finding showed that growth and yield parameters were significantly (P< 0.05) affected by fertilizer application. The result also revealed that accession OUSAI recorded the highest grain yield of 1015.10 kg/ha and NFAS4 recorded the least grain yield of 713.23 kg/ha. Also, the most lodged accession was OUAS1 which recorded 65% lodging of its total plant population and the least lodged accessions (NFAS4 and EYAS5) recorded about 10% lodging each. There was significant (P ˂ 0.05) variations among accessions for most of the attributes measured. The interactive effect of fertilizer and accession was significant ((P˂0.05) for most of the traits studied.